2021
DOI: 10.1186/s12882-021-02314-0
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue characteristics on dialysis and non-dialysis days in patients with chronic kidney failure on maintenance hemodialysis

Abstract: Background Fatigue is prevalent in hemodialysis patients who for survival follow a strict dialysis treatment regimen – dialysis and non-dialysis days. As a result, the daily activities, symptom burden, and clinical outcomes of hemodialysis patients vary significantly between dialysis and non-dialysis days. Fatigue is one of the most reported debilitating symptoms by hemodialysis patients with profound negative impact on their quality of life. Prior studies assessed fatigue during the preceding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 43 publications
0
14
0
2
Order By: Relevance
“…Several studies showed that fatigue in patients receiving HD is associated with poor outcomes, including reduced sleep quality 125 , poor quality of life (QOL) 126 , increased CVD 127 , increased hospitalization 127 and increased all-cause mortality 125 , 127 . Fatigue is most severe on dialysis days compared with non-dialysis days 128 .…”
Section: Global Patient-reported Outcomesmentioning
confidence: 99%
“…Several studies showed that fatigue in patients receiving HD is associated with poor outcomes, including reduced sleep quality 125 , poor quality of life (QOL) 126 , increased CVD 127 , increased hospitalization 127 and increased all-cause mortality 125 , 127 . Fatigue is most severe on dialysis days compared with non-dialysis days 128 .…”
Section: Global Patient-reported Outcomesmentioning
confidence: 99%
“…Fatigue is commonly experienced by patients undergoing hemodialysis and has a negative effect on their quality of life [ 1 ]. Its prevalence rate ranges from 60-97% among hemodialysis patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, the disease and treatment characteristics and physiological indicators could not be controlled for. The factor that fatigue may be higher on the day of dialysis [ 17 ] was not considered. Fourth, recall bias could have occurred because subjectively perceived QoL and the level of related factors were identified.…”
Section: Limitationsmentioning
confidence: 99%
“…Fatigue is one of the most common symptoms complained of by more than 70% of patients on dialysis [ 11 ]; it is known that the cause of this fatigue is related to demographic factors, physiological conditions, psychological conditions, biochemical factors, and behavioral factors [ 15 , 16 ]. Patients have the highest level of fatigue immediately after dialysis but may complain of fatigue symptoms, such as weakness, lack of energy, and poor concentration, even on those days without dialysis [ 17 ]. These factors cause patients to experience fatigue and low QoL.…”
Section: Introductionmentioning
confidence: 99%